Breaking the Saturated Vapor Layer with a Thin Porous Membrane - Yaoling Zhang; Fei Guo (Membranes, 2022)
The main idea of membrane distillation is to use a porous hydrophobic membrane as a barrier that isolates vapor from aqueous solutions. It is similar to the evaporation process from a free water surface but introduces solid–liquid interfaces and solid–vapor interfaces to a liquid–vapor interface. The transmembrane mass flux of a membrane-distillation process is affected by the membrane’s intrinsic properties and the temperature gradient across the membrane. It is interesting and important to know whether the evaporation process of membrane distillation is faster or slower than that of a free-surface evaporation under the same conditions and know the capacity of the transmembrane mass flux of a membrane-distillation process. In this work, a set of proof-of-principle experiments with various water surface/membrane interfacial conditions is performed. The effect and mechanism of membrane-induced evaporation are investigated. Moreover, a practical engineering model is proposed based on mathematical fitting and audacious simplification, which reflects the capacity of transmembrane flux.